Lambda Association and gay rights supporters demonstrate in front of Great America entrance - Sahl, Ted (photographer):::Creator::::::::::::
Lambda Association and gay rights supporters demonstrate with hand-made signs in front of the Great America entrance in Santa Clara in protest of the Great Outdoor Association's "gay" day.